2012
DOI: 10.2119/molmed.2012.00071
|View full text |Cite
|
Sign up to set email alerts
|

High Postoperative Blood Levels of Macrophage Migration Inhibitory Factor Are Associated with Less Organ Dysfunction in Patients after Cardiac Surgery

Abstract: Macrophage migration inhibitory factor (MIF) is an inflammatory cytokine that exerts protective effects during myocardial ischemia/reperfusion injury. We hypothesized that elevated MIF levels in the early postoperative time course might be inversely associated with postoperative organ dysfunction as assessed by the simplified acute physiology score (SAPS) II and sequential organ failure assessment (SOFA) score in patients after cardiac surgery. A total of 52 cardiac surgical patients (mean age [± SD] 67 ± 10 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 41 publications
4
29
0
Order By: Relevance
“…We found a 1000‐fold greater MIF concentration in the liver graft effluent than in recipients’ serum before and after reperfusion, suggesting that the human liver graft is a major source of MIF. Previous studies reported maximal MIF concentrations between 0.1 and 3.2 μg/mL in human blood . The marked release of MIF during human liver graft preservation observed in our study might trigger an inflammatory response within the liver graft.…”
Section: Discussionsupporting
confidence: 55%
“…We found a 1000‐fold greater MIF concentration in the liver graft effluent than in recipients’ serum before and after reperfusion, suggesting that the human liver graft is a major source of MIF. Previous studies reported maximal MIF concentrations between 0.1 and 3.2 μg/mL in human blood . The marked release of MIF during human liver graft preservation observed in our study might trigger an inflammatory response within the liver graft.…”
Section: Discussionsupporting
confidence: 55%
“…Comparable to sepsis, cardiac surgery with use of cardiopulmonary bypass (CPB) is associated with systemic oxidative stress and hemodynamic changes, resulting in a transiently decreased perfusion of organs, including the kidney. We and others have demonstrated that MIF is elevated during the perioperative inflammatory response after cardiac surgery (20,21). Several studies have revealed cardioprotective effects of MIF in the setting of acute myocardial I/R injury (20,22,23), but the functional role and clinical relevance of MIF in the development of postoperative AKI remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…MIF was shown to have antioxidant properties (20)(21)(22)(23)(24), potentially by its thiol-protein oxidoreductase (TPOR) activity. Here, we tested the hypothesis that MIF might be a protective factor limiting AKI through cytoprotective and antioxidative effects, using a comprehen-sive combined clinical and experimental approach including the stateof-the-art assessment of apoptosis, necroptosis, and ferroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, we did not observe any differences in serum MIF levels between control and RIPC treated patient after RIPC, supporting the other observations of no effects of RIPC. It should be noted however, that many values (25) were below the detection limit, and lower than observed in other studies with CABG patients [47, 48]. Therefore, these results should be interpreted with care.…”
Section: Discussionmentioning
confidence: 63%
“…Ischemia caused a release of MIF from the heart, which has been shown to be cardioprotective by regulation of AMPK signaling, inhibition of pro-apoptotic cascades and reducing oxidative stress [4547]. In CABG patients a perioperative increase in MIF was associated with enhanced antioxidant capacity and reduced organ dysfunction after cardiac surgery [47, 48]. We hypothesized that RIPC can increase MIF.…”
Section: Discussionmentioning
confidence: 99%